Wolf mountains : a history of wolves along the Great Divide - Jones, Karen R., 1972- (Parks and heritage series ;, 2002)
Documents the history of wolves in four Rocky Mountain national parks: Yellowstone, Glacier, Banff, and Jasper. Explores how changing scientific and emotional rationales facilitated the persecution and subsequent protection of resident canines.